Efeito da infecção pelo vírus da leucose enzoótica bovina na produção de leite e reprodução de rebanhos leiteiros - Daniela de Souza Rajao (2008)
Enzootic Bovine Leukosis (EBL) is a chronic viral disease of cattle, disseminated in Brazilian livestock. Although most infected animals are asymptomatic, the disease may cause considerable economic losses. Some infected animals may develop persistent lymphocytosis, which cause immunologic disturbs and can be related to productive loss. To evaluate the effects of bovine leukemia virus (BLV) infection on production and reproduction performances of milk cattle, 158 blood samples from lactating adult cows, crossbred Holstein/Zebu and purebred Holstein, were analyzed. Animals were divided into three groups: negative, positive without persistent lymphocytosis and positive with persistent lymphocytosis, according to Agar Gel Immunodifusion test (AGID) and leukogram results. Production and reproduction data were compared between groups, according to breed. Holstein infected females showed lower milk yield than uninfected ones, with a loss of 628.2 liters per lactation. Mixed breed positive cows showed higher production (in 440.8 liters) than negative ones. There were no differences between reproductive parameters of infected and non infected females. These results indicate an association between BLV infection and production of infected herds